Cystatin C as an Early Biomarker for Acute Kidney Injury: A Systematic Review - Syah Habib Aji Putra; Chobieta Paninda Arethusa Putri (Journal of Healthcare and Biomedical Science, 2026)
Acute kidney injury (AKI) remains a major clinical problem associated with increased morbidity, mortality, prolonged hospitalization, and rising healthcare costs. Serum creatinine, the conventional biomarker used for AKI diagnosis, has several well-recognized limitations, including delayed elevation after renal injury and susceptibility to non-renal influences such as age, sex, muscle mass, and hydration status. In recent years, cystatin C has gained attention as a potentially more sensitive biomarker because of its relatively constant production rate and earlier response to changes in glomerular filtration. This systematic review aimed to evaluate the diagnostic performance and clinical applicability of cystatin C for the early detection of AKI across diverse clinical settings. A comprehensive literature search was conducted in PubMed, Scopus, and Google Scholar for studies published up to December 2025. Eligible studies included human subjects at risk of AKI, assessment of serum or urinary cystatin C, and the use of recognized AKI diagnostic criteria. Study selection and data extraction were performed using predefined eligibility criteria, and findings were synthesized narratively because of substantial methodological heterogeneity among studies. The included studies consistently indicated that cystatin C may detect AKI earlier than serum creatinine in several clinical contexts, particularly in intensive care units, cardiac surgery, and contrast-induced nephropathy. Across studies, cystatin C generally demonstrated moderate-to-high diagnostic sensitivity and specificity; however, considerable variability was observed in cutoff values, sampling time, patient characteristics, and reference standards. Several studies also reported high negative predictive value, suggesting potential utility in excluding AKI in selected populations. Nevertheless, the diagnostic performance of cystatin C appeared to be influenced by multiple confounding factors, including systemic inflammation, corticosteroid therapy, thyroid dysfunction, and fluid balance status. Overall, current evidence suggests that cystatin C is a promising biomarker for the early detection of AKI and may provide diagnostic advantages over serum creatinine in specific clinical settings. However, existing evidence predominantly supports diagnostic accuracy rather than direct improvement in patient-centered outcomes. Further large-scale prospective studies are needed to establish standardized cutoff values, clarify optimal clinical application, and determine whether cystatin C-guided strategies improve clinical outcomes.